Yönetsel performans değerlendirmesi ve bir örnek uygulama - Çelik, Eser (My University, 1999)
Genel görüşe göre, değerlendirme yöntemleri bulunduğu düzeyi görmesi açısından çalışanın kendisine, kuruluşun genel performansı gözlemlenmesi bakımından yöneticiye ve sağlıklı bir karşılıklı tartışma ortamını olanaklı kılması sayesinde de kuruluşa önemli yararlar sağlamaktadır. Söz konusu yöntemler, oluşturulma ve uygulama aşamalarında potansiyel sorunlarla yüz yüze olmasına karşın, pek çok kuruluş yıllık amaç ve hedefler saptama hususuna önem vermekte ve bu yöntemlerin geliştirilmesi konusunda çaba göstermektedir. Bunun yanında performans değerlendirmenin ücret zamları ile ilgili olarak kullanılması konusunda önemli bir eğilim olduğu gözlenmektedir. Her ne kadar çalışanlarla ilgili potansiyel / terfi değerlendirmesi bazı işletmelerde performans değerlendirmesinden ayrı ise de , pek çok kuruluşta hala değerlendirme prosedürünün bir parçası olma özelliğini taşımaktadır. Personel Yönetimi Enstütüsü'nün yukarıda bahsedilen araştırması, kuruluşların % 71'inde performansın değerlendirme prosedürünün potansiyel ve terfi olanaklarının belirlenmesinde kullanıldığını göstermektedir. Bazı durumlarda söz konusu olanaklar için ayrı formlar düzenlenirken, diğer hallerde değerlendirmenin bu hususu kapsayan kısmı çalışana gösterilmemekte ya da görüşmeden sonra doldurulmaktadır. Potansiyel / terfi olanaklarının gözden geçirilmesine ilişkin bir bölümün değerlendirme prosedürüne dahil edilmesi çeşitli yönlerden eleştirilmektedir. Bu eleştiriler öncelikle gelecekteki performansın tahmin edilmesinin güçlüğü ve bu tahminde kullanılan bilginin geçerliliği üzerinde durmaktadır. Orta kademe yöneticiler gelecekteki potansiyeli ancak geçmiş performansı göz onüne alarak değerlendirmektedir. Bu durum başta makul gözükmekle birlikte daha üst düzeydeki iş taleplerini dikkate almayabilmektedir. Birinci amir performansı değerlendirme açısından en elverişli konumda olmasına rağmen kendisinden daha yüksek kademelerdeki veya değişik bölümlerdeki iş talepleri hakkında yetersiz bilgiye sahip bulunabilmektedir. Potansiyel / terfi değerlendirme prosedürleri aynı zamanda bunları uygulayan orta kademe yöneticilerin karşılacağı sorunlar bağlamında da eleştiriye uğramaktadır. Tipik olarak bunların en başında gelenleri, terfinin zamanlanması ile ilgili olup, cevabı 'bu yıl , gelecek yıl, bir ara, hiçbir zaman aralığında değişen evrelerdir. Bunlara ilave olarak çalışanın yükselebileceği en üst kademeyi sorgulayan sorulara verilen cevapların sağlığı da yöneticilerin yüksek seviyede anlayış, sezgi ve tahmin becerisine bağlıdır. Potansiyel / terfi değerlendirmesinin performans değerlendirmesinden ayrı tutulmaya başlanması pek çok gözlemci tarafından memnuniyetle karşılansa da; aslında bu devrim geçmişe göre terfi imkanlarının azalması sonucu değerlendirme sistemlerinde daha az yer alması olarak da yorumlanabilmektedir. Bununla birlikte değerlendirme merkezlerinin, psikolojik testlerin ve kariyer danışmanlığının giderek artan oranda kullanımı bunun tam tersini ortaya koymaktadır. Kuruluşlar artık geleceğin üst düzey yöneticilerinin gelişimini şansa bırakmamakta ve daha sistematik ve profesyonel bir yaklaşım için gerekli zaman ve para yatırımının gerçekleştirilmesi yoluna gitmektedir. Değerlendirme merkezlerinde bireyler eğitimli uzmanlar tarafından gerçek hayat simülasyonları, testler ve grup tartışmaları gibi çeşitli teknikler kullanarak değerlendirmeye tabi tutulmaktadır. Bazı durumlarda bulgular performans değerlendirmesi, personel ve yönetim geliştirme unsurlarının görüşleri gibi diğer bilgilerle birleştirilmekte, bireyin kendisiyle de tartışılarak pontasiyel değerlendirme başlığı altında bir rapor ortaya konulmaktadır. Söz konusu rapor çoğu zaman bireyin kendisi ve şirketi tarafından gelecekteki gelişimi için yapılması gerekenleri de içerebilmektedir.

1.Performance and Performance Management Performance is a natural outcome of both intelligence ability and motivation. Perfomance management systems aim at measuring and evaluating the employee's both individual and professional abilities according to the criteria objectively predefined to reach to the target and the satisfaction realizing their need for training and development of the employees to form the basic data for the management of carrier planning and scale of salaries. Performance management serves to reach the target to direct the performance of the employees and form the feedback mechanism for the employee to develop in his/ her profession and prepare for the future. In order to reach the target, both the manager and the employee should be objective, clear, sensitive to the needs and expectations of the other party, open to develop and help developing directing rather than judging. Besides the minimum qualifications like to accomplish the job like the willing, for what and how the performance will be performed should be indicated clearly. At this point, it would be useful to mention TARGET MODEL which should be considered as a whole in an affective performance management (HERSEY and GOLDSMITH MODEL) . 1)Ability: The required knowledge, skill, experience and personal qualifications to accomplish the job, 2)To be clear: To realize and accept what will be done when and how, 3)Organizational Support: To accomplish, the job, the required budget and other equipment be forwarded by other departments and human resources department. 4)Motivation: Being aware that the accomplished jobs will be awarded either secretly and openly. 5)Observation and Direction: Daily evaluation and directing before the periodical performance appraisal, 6)Validity: The legal conformity of the rules and their application to the company defined by the management practice. 7)Environment: The influence of the changing market conditions and government applications. Performance management feature 3 main points A.Performance Planning B.Directing Assisting C.Performance Appraisal The way we evaluate performance management requires these three functions should feature together in the same process. A.PERFORMANCE PLANNING Performance planning can be defined as an important management activity determined at the beginning of the performance planning period, where the targets and the strategies to reach these targets are discussed and decided. The traditional management practice puts forward the idea both the managers and employee to define the targets together, new dynamic leadership practice shows as that that this can be valid only for the medium size employees where, an atmosphere should be created for the top level success employees with feature to take responsibility and define the strategies should practiced. Besides this practice of dynamic leadership comprehension will be applied during the performance planning period, the employees would be aware of the area the managers move in order to reach the target and this will help to reduce the unnecessarily tension and prevent the surprises. The variables of the TARGET MODEL mentioned in the previous page of performance planning should be used altogether. Apart from this a manager, by preparing the answers to following questions, can foresee what can be the positive outcomes, avoiding the negative ones and which way to take to accomplish the missing points: ·Whether know-how is clearly defined? ·What is the organizational support? ·Whether the process defined for informing and directing? B.DIRECTING AND ASSISTING Dynamic leadership practice plays a great role in managers' assessing the connections between the targets defined in performance planning process and the success lines of the employees in reaching these targets. What the managers mostly fail to notice is moving onto directing and assisting phase before the paper analysis of variables of target model. If the performance problems are conveyed as soon as possible, the solution will be reached shortly and many conflicts will be avoided. C.PERFORMANCE APPRAISAL What is expected at the very beginning of a performance appraisal is that it won't end with a surprise either for the manager or the employee. The performance appraisal will be a natural outcome of the evaluation of the past period both for the employee and the manager, rather than a nightmare, if the variables of Target Model in performance planning and directing assisting processes and the principles of dynamic leadership which will be mentioned later as are considered properly. In final performance appraisal, how much for the standards defined in performance planning process drawn, accomplished and furthermore improved are analyzed. If the performance problem is agreed upon, the manager and the employee should convey the reactions and decisions which will be leading within solutions to overcome the problem. At this stage again the accurate analysis of the variables of Target Model will play an important role in defining the possible future training transfer and personnel related decisions and whether the reason for distraction from performance standards is caused by the employee, the organization environmental facts or the administration. What we should keep in mind is the fact that there can never be the best or the most accurate in solving the problems related to people. III. PERFORMANCE APPRAISAL A.Introduction: Performance appraisal is an evaluation through the employer evaluates the employee's performances in job by comparing and assessing the predefined standarts. This is a systematic process in which good performance is evaluated, awarded and to be developed are established. Performance appraisal process should be approached through two different perspectives: organizational and individual. Organization focuses on the support of performance appraisal results in total on company where individual on reaching the targets successfully. The main reasons for performance management and performance appraisal as the basics of human resources planning process as listed: ·Performance assessment, ·Potential and promotion capacity, ·Career planning and development process, ·Supporting planning and control. B.History: Performance appraisal is perceived as a formal procedure on whom the appraisal is conducted. Appraisal formats are originated in the USA, yet has been practiced in the United Kingdom since 60's-70's. Many surveys are conducted accordingly due to the defaults in appraisal formats and difficulties faced by the employer during the performance appraisals. Despite the difficulties faced by the employer, every employer is aware of the useful outcomes of performance appraisal when accomplished properly; for the employees for the employer and for the institution. The related surveys are carried for the welfare of the process through recognition of current problems. The most frequently encountered problems are: ·Subjective approach in performance appraisal; ·Centralist tendency (only a few criteria applied/ based), ·Unnecessary (in number and accuracy) documentation, ·Assessment according to unrelated targets, ·Different tendencies among the managers. Many institutions aiming at solving some of the problems mentioned above made some adaptations and developed kinds of procedures to make the application objective. One of the methods recently observed focuses on evaluation the performances of employees according to the predefined target and level of accomplishment rather than their personalities. Management based on targets, besides being an approach of management, is also typical example of performance evaluation system based on results . Management Through Targets which emerged in 1960s and at the beginning 1970s is a result of this tendency. Management through Targets in fact both carries a wider content and also is one of the main element of performance evaluation system. Management through Targets states the combined aims understood mutually by different units and classifying the targets of the institution. (For example Marketing Department accepts to sell the credit provided by Finance Department). However many Management through Targets principles apply only to a limited area. It is obvious that approach on evaluation based on outcomes or outputs are healthier than the evaluation based on personalities or inputs. Literature forming evaluation systems stresses especially the possible discordance among the targets put forward. Before, the existing performance was connected to salary, which caused the employee accept his/ her deficiencies and led the employees to show defensive and reluctant attitude; which eventually today the employees of the systems not related to salary evaluate the choice of the employer as an incorrect one. Recently the difficulty in evaluation of determining the existing performance (can be done only by the best and first superior) together with potentially best performance realized (=promotion) (can be determined by a top level manager superior than the first one) is put forward. As a result, some of institutions created different procedures apart from evaluation systems to determine the potential growth and development. A survey conducted by the Personnel Evaluation Institute, among 306 institutions during 70s and 80s, on performance evaluation systems showed that evaluation systems continuously lose their significance in determining the potentials such as future promotion and salary management. 1970%1980% Determining Training and Development Potential9697 Developing the Existing Performance9697 Revise the Past Performance 9298 Determine the Future Promotion Possibility9171 Assisting Performance Targets9181 Appraisal of new salary level5740 It was only the managers who were evaluated. Today the spectrum of the evaluated ones has been enlarged. For almost every employee job descriptions are considered and evaluation is conducted through different methods. Again today, performance evaluation system which was perceived differently from the one mentioned above is not considered free from the system of promotion and salary management in many institutions. G. Results of Performance Evaluation: 4 main functions of performance evaluation leading to results are; 1)Each person has enough feedback on his/ her performance, 2)Serving as an improving and developing action to form effective job habits, 3)Providing the sufficient data to managers for determining the future rotations and career planning processes, 4)Effecting on salary and bonus system. As it is seen performance evaluation is a necessary format to be formed for the communication of job activities. Besides, it is a good opportunity to convey the best performance, reward and the required areas to be developed. The positive effects of performance evaluation; For the organizationFor the individual Performance appraisal and determination of systematic targetsDetermination the expectations of the employer under the umbrella of efforts and performance Establishment of an effective relationship for long term benefitsConfidence in individual by awareness of performance evaluation standards As a result, qualitative performance evaluation is possible when the evaluator and the evaluated conform predefined processes fully and the decision processes are carried out refined from prejudices and as objective as possible. V. CONCLUSION Generally accepted that evaluation methods are for the benefit of the employee as it shows his/ her current level, for the benefit of manager as it helps observe the general performance of the institution and for the benefit of institution by forming healthy interactive discussion atmosphere. Although the methods mentioned face potential problems during the formation and application levels, many institutions emphasize annual aims and targets and make effort to develop these methods. Apart from this, it is also observed that there is a substantial tendency of using performance appraisal for salary increases. However, in many institutions potential/ promotion evaluation separated from performance evaluation, it is still an important part of evaluation procedure in many institutions. The survey mentioned above of by the Personnel Management Institute, showed that for 71% of the institutions performance evaluation procedure is used for determination of potential and promotion possibilities. While in some cases separate forms are designed for mentioned possibilities, in other cases this part of the evaluation is not either shown to the employee or filled after the interview. Including the part of potential/ promotion possibilities' revision is criticized in many ways. These critics primarily well upon the difficulty of estimation of future performance ad the validity of information used in this estimation. Middle level managers evaluate performance only through revising the part performance. Although this may seem reasonable at the beginning, it will not take into considerations when higher level job requests arise. Despite the first superior is available person for evaluation of performance for the requests of higher level of different departments, he/ she can lack sufficient information. Potential promotion evaluation procedures are criticized in the context of the problems middle level managers face while applying these procedures. Typically, the most forthcoming ones are related to the timing of promotion where the answer changes in the stages this year, next year, sometime, never. Additionally, the reliability of the answers given to the questions examining the employee's possible highest stage promotion is related to the high level of comprehension, intuition and estimation skills. Although separation of potential/ promotion evaluation form performance evaluation is welcome by many observers, in fact this revolution can be commended as appearing little in performance evaluation as a result of decreased promotion possibilities when compared to past. However continuously increasing usage of psychological tests and career consultancy by evaluation centers convey the opposite. Institutions leave no place for luck for the evolution of future top level managers and choose the way of approach of a more systematic and professional which enables required time and money investment. In evaluation centers individuals are evaluated through different techniques such as real life simulations, tests and group discussions by educated professionals. In some cases, findings are put together with the performance evaluation, the views of personnel and management development elements with other information and a report is presented along with a discussion of with the individual under the name of potential evaluation. Mentioned report many times include the requirements both for the development of individual and the corporate. The appendix includes an example of Performance Evaluation Form, examples of Performance Evaluation Form from Central Asian countries and flow diagrams of performance evaluation processes of Malaysian Agricultural Development Bank
Keywords: Performans Değerlendirme